Teneurins assemble into presynaptic nanoclusters that promote synapse formation via postsynaptic non-teneurin ligands - Xuchen Zhang; Pei-Yi Lin; Kif Liakath-Ali; Thomas C. Südhof (Nature Communications, 2022)
Abstract Extensive studies concluded that homophilic interactions between pre- and postsynaptic teneurins, evolutionarily conserved cell-adhesion molecules, encode the specificity of synaptic connections. However, no direct evidence is available to demonstrate that teneurins are actually required on both pre- and postsynaptic neurons for establishing synaptic connections, nor is it known whether teneurins are localized to synapses. Using super-resolution microscopy, we demonstrate that Teneurin-3 assembles into presynaptic nanoclusters of approximately 80 nm in most excitatory synapses of the hippocampus. Presynaptic deletions of Teneurin-3 and Teneurin-4 in the medial entorhinal cortex revealed that they are required for assembly of entorhinal cortex-CA1, entorhinal cortex-subiculum, and entorhinal cortex-dentate gyrus synapses. Postsynaptic deletions of teneurins in the CA1 region, however, had no effect on synaptic connections from any presynaptic input. Our data suggest that different from the current prevailing view, teneurins promote the establishment of synaptic connections exclusively as presynaptic cell-adhesion molecules, most likely via their nanomolar-affinity binding to postsynaptic latrophilins.